Modeling quality, satisfaction and perceived crowding in public healthcare: A study with low-income Brazilian patients - Marcato, João Guilherme [UNESP]; Da Silva, Hermes Moretti Ribeiro [UNESP]; Luiz, Octaviano Rojas [UNESP]; Mariano, Enzo Barberio [UNESP]; Paro, Carlos Eduardo (FapUNIFESP (SciELO), 2023)
This paper is one of the first to propose a research model to assess the quality and satisfaction perceived by low-income Brazilian patients using public healthcare services, under the moderating effect of perceived crowding. The model was evaluated from data obtained from 417 patients, and its proposed relationships and statistics were tested through Structural Equation Modeling using a Partial Least Squares approach (PLS-SEM). To explore the moderating effect of perceived crowding, the sample was divided into two groups and tested by employing multi-group analysis (MGA). The results show that Reliability, Safety, Tangibles, Empathy and Responsiveness have a positive effect on Perceived Healthcare Quality (PHQ), which, in turn, has a marked effect on patient satisfaction (PS), ergo, PHQ acts as antecedent of PS. However, perceived crowding has no moderating effect on any relationship in the model.
Modelando qualidade, satisfação e crowding percebido em saúde pública: um estudo com pacientes brasileiros de baixa-renda
Keywords: Low-income patients; Patient satisfaction; Perceived crowding; Public healthcare; Quality management; Service quality